Effects of l-carnitine in the distillers dried grains with solubles diet of sows on reproductive performance and antioxidant status of sows and their offspring. (23rd November 2018) - Wei, B.; Meng, Q.; He, S.; Qu, Z.; Nie, S.; Shi, B.; Shan, A.
Abstract : Distillers dried grains with solubles (DDGS) are highly susceptible to lipid oxidation because DDGS contain about 10% crude fat, which is largely composed of polyunsaturated fatty acids. l -carnitine serves an important function in fatty acids β -oxidation, and also has antioxidant properties. The objective of this study was to examine the effects of l -carnitine in the DDGS diet of gestating and lactating sows on reproductive performance, milk composition and antioxidant status of sows and their offspring. One hundred and twenty sows (Landrace×Large white, mean parity 4.2, initial BW 230 kg) were randomly allotted to 1 of 4 dietary treatments ( n =30 sows/treatment). Treatments were arranged as a 2×2 factorial with two levels of dietary DDGS (0 v . 250 g/kg in gestating diets and 400 g/kg in lactating diets) and two levels of dietary l -carnitine (0 v . 100 mg/kg in gestating diets and 0 v . 200 mg/kg in lactating diets). Distillers dried grains with solubles had no significant effect on litter size but significantly reduced the birth weights and weaning weights of piglets ( P <0.05). Distillers dried grains with solubles reduced the antioxidant enzyme activities ( P <0.05) and increased the malondialdehyde level in the plasma of sows on day 60 of gestation ( P =0.004) and day 14 of lactation ( P =0.008). The compositions of colostrum and milk were not affected by inclusion of DDGS and dietary l -carnitine ( P >0.05). Supplementing the diets with l -carnitine had no significant effect of total litter size ( P >0.05) but increased the number of piglets born alive and piglets weaned, birth weight and weaning weight of piglets and litter weight at birth and weaning ( P <0.05). l -carnitine supplementation also increased the concentration of l -carnitine in milk and l -carnitine status of piglets ( P <0.05). The antioxidant enzyme activities of new born and weaning piglets were increased ( P <0.05) by maternal dietary l -carnitine but this did not extend to finishing pigs. In conclusion, including DDGS in the sows diet could induce oxidative stress, which may be associated with the reduced individual birth and weaning weight of piglets. Dietary l -carnitine supplementation improved the antioxidant and l -carnitine status of sows, which may be associated with the improved reproduction and piglet performance and the antioxidant status of piglets at birth and weaning. There were no interactions between DDGS and l -carnitine.